Enzyme inhibitory and antioxidant investigations of Tetracera macrophylla Vall. and Entada spiralis Ridl. and isolation of active principles - Opeyemi Roheem, Fatimah; Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton (2017)
Diabetes is a serious global health problem that affects over 422 million citizens (WHO, 2014). It is characterized by hyperglycemia, (abnormal increase in plasma glucose level) resulting from hydrolysis of starch by pancreatic α- amylase and glucose uptake by intestinal α- glycosidase. Inhibitors of these two enzymes have been suggested to be better candidates in preventing diabetes and its complications. Pancreatic α- amylase is an enzyme that helps in the hydrolysis of starch into maltose prior to absorption.α- glucosidase enzyme catalyses the breakage of disaccharide to glucose, inhibiting these enzymes retards the dietary carbohydrate uptake and supress the postprandial hyperglycemia. Therefore, the most effective strategy of controlling diabetes is to inhibit the actions of these enzymes (Apostollidis & Lee, 2010; Striegel et al., 2015. Additionally Free radicals are considered as a major causative factor of cell damage that degenerate into chronic diseases such type 2 DM, liver problem, stroke and cancers. From ancient times antioxidants from herbal extracts and drinks were utilized and many have been proved to improve antioxidant capacity and therefore prevent cell and tissue damage. Tetracera macrophylla Vall (family: Dilliniacea) is an evergreen climber that widely spreads across Sumatra, Peninsula Malaysia, Bangka and Borneo and some parts of Africa. . It plays an important role in traditional herbal medicine for curing many ailments. Similarly, Entada spiralis Ridl (Family : leguminosae) locally known as Beluru or Sintok is a woody climber that can grow up to 25 m tall, possessing a wide range of ethno medicinal uses. Many species of Entada and Tetracera have been scientifically investigated on several ailments, these plants lacks scientific record to proof their vast medicinal uses, this research therefore aim to investigate the inhibitory capacity of these plants on digestive enzymes and free radicals as many species of the genus have been validated for these activities.